Effect of use of duckweed powder as a fish feed on monoculture of silver carp (Hypophthalmichthys molitrix) - Hasan, K; Rahman, MS; Sultana, S; Shahjahan, M (International Journal of Agricultural Research, Innovation and Technology, 2019)
An experiment on the use of duckweed powder as a fish feed on monoculture of silver carp (Hypophthalmichthys molitrix) was conducted in 6 ponds for a period of 75 days. The area of the each pond was one decimal. The experiment was carried out under two treatments, each with 3 replications. A combination of duckweed powder and rice bran at the ratio of 3:1 was supplied at the rate of 4% of total body weight in the ponds under treatment-I. On the other hand, the ponds under treatment-II were without supplying of feed. Each of the ponds under both treatments were stocked with 45 fingerlings of silver carp (H. molitrix). The average initial length and weight of the fingerlings were 14.60 cm and 33.48 g, respectively. The ponds were fertilized fortnightly with poultry droppings at the rate of 2 kg, urea 60 g and TSP 90 g decimal-1. During the experimental period the ranges of physico-chemical parameters viz. water depth (0.82 to 0.90 m), water temperature (17.80 to 26.7 °C), air temperature (19.11 to 28.29 °C), transparency (28.00 to 34.00 cm), dissolved oxygen (6.70 to 8.20 mg L-1), pH (6.70 to 8.00), total alkalinity (170 to 210 mg L-1), free CO2 (0.0 to 3.50 mg L-1), phosphate-phosphorus (1.2 to 2.9 mg L-1), and nitrate-nitrogen (3.1 to 4.5 mg L-1) were within the productive limit and more or less similar in all the ponds under treatments I and II. There were 25 genera of phytoplankton under four major groups and 10 genera of zooplankton under three major groups in the experimental ponds. Mean survival rates under treatment-I and treatment-II were 97.78% and 95.56%, respectively. The specific growth rates (SGR % per day) of the fish found under treatment-I and treatment-II were 0.98% and 0.49%. The calculated net production of the ponds under treatment-I was 1.87 ton ha-1 yr-1 and that of the ponds under treatment-II, was 0.74 ton ha-1 yr-1. By 't' test, it was found that the net fish production of treatment-I was significantly (p<0.01) higher than that of treatment-II, and cost return relationship was found that the net profit of treatment-I and treatment-II were more or less similar. Finally, it can be concluded that duckweed powder as an ingredient of fish feed had significant impacts on production of silver carp, which do not consume duckweed as fresh and raw condition. Thus, duckweed powder can be used as feed for most fishes. Int. J. Agril. Res. Innov. & Tech. 9 (1): 73-83, June, 2019